이산화탄소/프로필렌옥사이드 공중합용 고활성 촉매 제조방법 - 민재기 (The Graduate School, Ajou University, 2009)
A highly active catalytic system for CO2/(propylene oxide) copolymerization was prepared based on the concept of a system containing a Lewis acidic metal center and quarternary ammonium salts units. The catalytic system showed high activity (TON >20000; TOF >20000 h-1) even at high temperature and high [epoxide]/[catalyst] ratio and selectively producing a very high molecular-weight copolymer (Mn, 300,000). The catalyst can be easily separated by filtration through a short pad of silica gel to obtain polymer containing negligible amounts of metal residue (1-2 ppm). The separated catalyst can be reused without significant loss in catalytic performance.
학위논문(석사)--아주대학교 일반대학원 :분자과학기술학과,2009. 2
Keywords: 이산화탄소; 공중합; 살렌타입 균일촉매